2020
DOI: 10.1039/d0cp00380h
|View full text |Cite
|
Sign up to set email alerts
|

Quick-EXAFS and Raman monitoring of activation, reaction and deactivation of NiCu catalysts obtained from hydrotalcite-like precursors

Abstract: MCR-ALS analysis of Quick-EXAFS combined to Raman provide insight into activation/reactivity and deactivation of NiCu-catalysts used for Ethanol Steam Reforming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…S4a). 30 Fourier-transformed extended X-ray absorption fine structure (FT-EXAFS) of the Ni K-edge showed that the peaks of Ni in Ni SA/CeO 2 were totally different from the curve of Ni in NiO (Fig. 1g) but similar to the curve of Ce in CeO 2 .…”
Section: Resultsmentioning
confidence: 98%
“…S4a). 30 Fourier-transformed extended X-ray absorption fine structure (FT-EXAFS) of the Ni K-edge showed that the peaks of Ni in Ni SA/CeO 2 were totally different from the curve of Ni in NiO (Fig. 1g) but similar to the curve of Ce in CeO 2 .…”
Section: Resultsmentioning
confidence: 98%
“…The D/G ratio of catalysts based on alumina as support, customarily related to high ordered coke formation, is estimated to � 2, while the average in the catalysts studied here was 0.4. [46] For the sample reduced at 700 °C, the combined bands R1 and R2 represent more than 80 % of the coke in Ni 10 MgO catalyst. It suggests that the catalyst had more significant deactivation even though the predominant amount of carbon is formed by monoatomic carbon.…”
Section: Analysis Of the Spent Catalystsmentioning
confidence: 98%
“…Some studies have suggested the possibility of amorphous carbon deposits also being responsible for deactivation [66,67]. However, the lower total amount of coke produced in the presence of small particles is a general factor for the maintenance of catalytic activity [68].…”
Section: Stability and Analysis Of The Spent Catalystsmentioning
confidence: 99%